Association between cognitive restraint, emotional eating, uncontrolled eating, and body mass index among health care professionals - Rasha Mohammad Alqahtani; Amani Alhazmi (Scientific Reports)
Abstract Among healthcare professionals (HCPs), the demanding nature of their work, irregular schedules, and high-stress environments can significantly influence their eating behaviors. This study’s objectives were to assess the relationship between cognitive restraint (CR), emotional eating (EE), uncontrolled eating (UE), and body mass index (BMI) and identify the sociodemographic factors associated with CR, EE, and UE among HCPs. A cross-sectional study and a simple random sampling technique were employed. Data on sociodemographic characteristics and anthropometric measurements were gathered using a self-administered online questionnaire. Eating behaviors (CR, EE, UE) were assessed using the Three-Factor Eating Questionnaire—Revised 18 Items. Of the 400 HCPs, 37.3% of their BMIs fell within the overweight range, and 22.5% fell within the obesity range. The overall mean score of CR among participants was 67.5 ± 26.4, UE was 42.1 ± 22.8, and EE was 38 ± 26.9. BMI was significantly associated with UE (B = 0.523, p = 0.026) and EE (B = 0.612, p = 0.014), suggesting that higher BMI levels are related to greater tendencies toward both behaviors. These findings underscore the need for tailored interventions and support programs to address these eating behaviors among HCPs. Such interventions are vital to promote healthier eating behaviors, improve overall well-being, and ultimately enhance the quality of healthcare these professionals provide.